Tis21 is required for adult neurogenesis in the subventricular zone and for olfactory behavior regulating cyclins, BMP4, Hes1/5 and Ids - Farioli-Vecchioli, Stefano; Ceccarelli, Manuela; Saraulli, Daniele; Micheli, Laura; Cannas, Sara; D'Alessandro, Francesca; Scardigli, Raffaella; Leonardi, Luca; Cinà, Irene; Costanzi, Marco; Mattera, Andrea; Cestari, Vincenzo; et al. (Frontiers in Cellular Neuroscience, 2014)
Bone Morphogenic Proteins (BMPs) and the Notch pathway regulate quiescence and self-renewal of stem cells of the subventricular zone (SVZ), an adult neurogenic niche. Here we analyze the role at the intersection of these pathways of Tis21 (Btg2), a gene regulating proliferation and differentiation of adult SVZ stem and progenitor cells. In Tis21-null SVZ and cultured neurospheres, we observed a strong decrease in the expression of BMP4 and its effectors Smad1/8, while the Notch antineural mediators Hes1/5 and the bHLH inhibitors Id1-3 increased. Consistently, expression of the proneural bHLH gene NeuroD1 decreased. Moreover, cyclins D1/2, A2 and E were strongly up-regulated. Thus, in the SVZ Tis21 activates the BMP pathway and inhibits the Notch pathway and the cell cycle. Correspondingly, the Tis21-null SVZ stem cells greatly increased; nonetheless, the proliferating neuroblasts diminished, whereas the postmitotic neuroblasts paradoxically accumulated in SVZ, failing to migrate along the rostral migratory stream to the olfactory bulb. The ability, however, of neuroblasts to migrate from SVZ explants was not affected, suggesting that Tis21-null neuroblasts do not migrate to the olfactory bulb because of a defect in terminal differentiation. Notably, BMP4 addition or Id3 silencing rescued the defective differentiation observed in Tis21-null neurospheres, indicating that they mediate the Tis21 pro-differentiative action. The reduced number of granule neurons in the Tis21-null olfactory bulb led to a defect in olfactory detection threshold, without effect on olfactory memory, also suggesting that within olfactory circuits new granule neurons play a primary role in odor sensitivity rather than in memory.